Peranan security concern dalam kenyamanan transaksi perbankan secara online dan dampaknya terhadap kinerja perbankan - Yuana Rizky Octaviani Mandagie; Indah Masri; Widyawati Widyawati; Fitri Angger Pangestu; Adinda Atmiard Sukma (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2022)
This study aims to examine the role of security concerns in the convenience of online banking transactions, which consist of the convenience of access, the convenience of transactions, and convenience of benefits, as well as seeing the impact on banking performance. This study uses primary data by distributing questionnaires to respondents from the Academic Community of FEB Univ Pancasila who use online banking transactions. The analysis method uses Structural Equation Model (SEM) with smart PLS. The results showed that the convenience of access was proven to improve banking performance. On the other hand, transaction convenience has a significant negative effect on financial performance, which means that the speed and ease with which consumers can complete transactions reduces financial performance; this may be due to the imperfect mobile banking application or weak internet networks. Likewise, security concern also shows a significant negative effect on financial performance, which means that consumer attention to the safety and security of transaction data and the security of personal information shared through banking platforms is still low, so customers who still feel insecure in online transactions can have an impact on the decline in banking performance